Deregulation of MicroRNA-146a and 155 expression levels might underlie complicated pregnancy in Toxoplasma Gondii seronegative women - Marwa M. Naguib; Youssef Abdel Zaher; Hemat Salah M. Ali; Hamasat Abdelhafiz Elnoury; Lina Abdelhady Mohammed; Omnia Youssef Habashy; Dina Abdelhady Mohammed (BMC, 2024)
Abstract Background To evaluate the ability of the estimated plasma expression levels of genes of microRNA (MiR-) 146a and 155 to differentiate between samples of pregnant women suspected to be infected by T. gondii. 50 newly pregnant women who had at least one of the criteria of high risk for toxoplasma infection and 50 newly primigravida women free of these criteria gave blood samples for qualitative determination of serum toxoplasma antibodies and estimation of plasma expression levels of MiR-146a and 155 using the qRT-PCR. During the pregnancy course, the incidence of pregnancy complications was recorded. Results Twenty-six women were IgM−/IgG−, 17 women were IgM+/IgG− and 7 women were IgM+/IgG+. Thirty-two women had pregnancy complications with significantly lower incidence in IgM−/IgG− women. Plasma expression levels of MiR-146a and 155 were significantly higher in total patients compared to control levels and were significantly higher in samples of IgM+/IgG+ patients than in other samples. Statistical analyses defined a high plasma level of MiR-155 as the highly significant predictor for oncoming pregnancy complications and high levels of both microRNAs as predictors for the presence of toxoplasmosis despite seronegativity. Kaplan-Meier regression analysis defined increasing cumulative risk of having toxoplasmosis despite seronegativity with plasma levels of MiR-146a and MiR-155 of 1.2 and 3, respectively. Conclusion The incidence of pregnancy complications is high, irrespective of the seronegativity of women at high risk of toxoplasmosis. Estimated plasma levels of MiR-155 might identify women liable to develop complications and differentiate seronegative women vulnerable to having T. gondii infection. Trial registration The study protocol was approved preliminarily by the Local Ethical Committee at Benha Faculty of Medicine. Before enrollment, the study protocol was discussed in detail with the study participants, and those accepted to participate in the study signed written fully informed consents. The final approval of the study protocol was obtained after the end of case collection and registered by RC: 5-11-2022.